WEBVTT
00:00:00.770 --> 00:00:14.170
Find the arithmetic sequence in which the sum of the first and third terms equals negative 142, and the sum of its third and fourth terms equals negative 151.
00:00:15.970 --> 00:00:20.370
We denote the first term of any arithmetic sequence by the letter π.
00:00:21.020 --> 00:00:24.150
The common difference is denoted by the letter π.
00:00:25.400 --> 00:00:29.280
This is the difference between each of the terms in the sequence.
00:00:30.120 --> 00:00:33.930
The second term of the sequence is, therefore, equal to π plus π.
00:00:35.150 --> 00:00:39.010
Adding π to this gives us the third term π plus two π.
00:00:40.320 --> 00:00:47.940
This pattern continues, giving us an πth term formula of π plus π minus one multiplied by π.
00:00:49.560 --> 00:00:56.100
We are told in this question that the sum of the first and third terms is negative 142.
00:00:57.380 --> 00:01:03.160
This means that π plus π plus two π is equal to negative 142.
00:01:04.520 --> 00:01:10.660
Simplifying this gives us two π plus two π equals negative 142.
00:01:12.230 --> 00:01:15.150
We could divide both sides of this equation by two.
00:01:15.550 --> 00:01:19.800
However, weβll work out the second equation in this question first.
00:01:20.990 --> 00:01:25.890
The third and fourth terms have a sum of negative 151.
00:01:27.080 --> 00:01:33.440
This means that π plus two π plus π plus three π is equal to negative 151.
00:01:34.660 --> 00:01:42.350
Grouping or collecting the like terms gives us two π plus five π is equal to negative 151.
00:01:44.050 --> 00:01:50.700
We now have two simultaneous equations that we can solve to calculate the values of π and π.
00:01:52.560 --> 00:01:57.390
When we subtract equation one from equation two, the πβs cancel.
00:01:58.760 --> 00:02:02.240
Five π minus two π is equal to three π.
00:02:03.370 --> 00:02:11.610
Subtracting negative 142 is the same as adding 142 to negative 151.
00:02:12.200 --> 00:02:14.350
This is equal to negative nine.
00:02:15.640 --> 00:02:21.460
Dividing both sides of this equation by three gives us π is equal to negative three.
00:02:22.930 --> 00:02:29.540
We now need to substitute this value into equation one or equation two to calculate π.
00:02:30.710 --> 00:02:40.010
Substituting into equation one gives us two π plus two multiplied by negative three is equal to negative 142.
00:02:41.390 --> 00:02:46.980
This simplifies to two π minus six is equal to negative 142.
00:02:48.380 --> 00:02:54.370
Adding six to both sides gives us two π is equal to negative 136.
00:02:55.580 --> 00:03:01.120
And finally, dividing by two gives us π equals negative 68.
00:03:02.350 --> 00:03:17.360
As the first term of the sequence is negative 68 and the common difference is negative three, then the arithmetic sequence is negative 68, negative 71, negative 74, and so on.